Géographie d’une maladie émergente en milieu urbain endémique, le cas de la dengue à Delhi, Inde - Olivier Telle (Unité Mixte de Recherche 8504 Géographie-cités, 2015)
Dengue is a tropical and sub-tropical disease whose etiological agent is a virus (the dengue virus, DENV). The virus is transmitted by mosquitoes. The major mosquito vector is Aedes aegypti which has adapted to urban conditions; Aedes albopictus is a secondary vector, occurring in more rural environments, but which has recently invaded Europe. Currently, an estimated 70-500 million people are affected by the virus every year in over a hundred countries across the world (DVI, 2010), mainly in urban areas. In the lack of an efficient vaccine (Sabchareon et al., 2011), an effective vector control by eliminating adult mosquitoes and removing potential egg laying sites, is the only way of checking the spread of the virus once there has been an outbreak of the disease in a given territory. However, the analysis realized in intra-urban areas does not clearly show a correlation between incidence and environment. This article aims at understanding the spatio-temporal diffusion of registered dengue cases in Delhi in 2008 and 2009. Ultimately, the objective is to understand the factors that will impact the geography of dengue.